LEGAL PROTECTION OF THE RIGHTS PERPETRATORS OF TERRORISM IN THE CRIMINAL JUSTICE SYSTEM IN INDONESIA - Siska Juwita Malau (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
Criminal acts of terrorism can be categorized as malum in se not including malum prohibitum. This is because terrorism is a crime against conscience, being evil not because it is prohibited by law but because terrorism is essentially a despicable act. Generally, police officers will determine a criminal offender if preliminary evidence is sufficient. Unlike the case with acts of terrorism, because this criminal act is a humanitarian problem that may receive the attention of many people, causing the police to be prosecuted to quickly uncover the perpetrators of terrorism crimes. As an alternative is possible, namely the confession of a suspect who has been caught. It is not an open secret that the Suspect of a criminal case, is unlikely to reveal what has been done or what his group is planning. So the disclosure of criminal acts of terrorism in terms of obtaining the confession of a suspect, there are many ways that investigators can do it. Among other things, through coercion, threats not even a few that end in physical violence or torture, but we must not be separated from the principle adopted in Indonesia regarding the principle of Presumption of Innocence, and against even perpetrators of Terrorism, this principle must also be applied, but still that we put forward the principle of Lex Specialeis Derogat Lex Generale. In the criminal justice system in Indonesia, the criminal justice mechanism as a process is referred to as the Criminal Justice Process which starts from investigation, arrest, search, detention, prosecution. The implementation of human rights in the Indonesian criminal justice system already regulates the rights of suspects and defendants, and also by prioritizing the principle of presumption of innocence, but nevertheless has not clearly and completely guaranteed the process of compensation, restitution, and rehabilitation of the protection of the rights of suspects/defendants suspected of being perpetrators of terrorism crimes.